Impact of COVID-19 and emotional states of Filipino university students - John Paul Palo Miranda; Julius Ceazar Gatchalian Tolentino (Institute of Advanced Engineering and Science, 2023)
The coronavirus disease (COVID-19) pandemic has extremely caused massive disruptions in the education sector, and this led to the adoption of full-distance learning modalities across different educational institutions worldwide. However, studies are still needed within the context of the Philippines in terms of the impact of the pandemic on university students in light of a gradual limited face-to-face transition. This study determined the Filipino college students’ perceived impact of the COVID-19 pandemic and the prevalence of depression, anxiety, and stress symptomatology (DASS) among them. This cross-sectional study surveyed Filipino university students from a public higher education institution in the Philippines via convenience sampling. A total of 3,718 students participated in the study. Analysis showed that despite the respondents’ level of DASS being roughly similar and normal, half of them is experiencing mild to extremely severe symptomatology. Further results indicated that there is a statistically significant difference in their DASS when grouped according to their gender and class level. The findings will be beneficial to multiple stakeholders in designing data-driven policies that would maximize the possibility of a safe resumption of limited, gradual, and eventually, full face-to-face modalities.